A feedback loop between NONHSAT024276 and PTBP1 inhibits tumor progression and glycolysis in HCC by increasing the PKM1/PKM2 ratio. Issue 4 (27th December 2022) - Li, Yuwei; Chen, Xia; Huang, Hengliu; Liao, Ling; Chong, Huimin; Li, Guangyao; Yuan, Tao; Lu, Weiping; Deng, Shaoli; Huang, Qing
Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies with a hallmark of aberrant metabolism. The mechanism of long noncoding RNAs (lncRNAs) underlying the aggressive behaviors and glycolysis of HCC is poorly understood. In this study, we identified, via microarray, novel lncRNA NONHSAT024276 as a potential tumor suppressor in HCC. The downregulation of NONHSAT024276 closely correlated with larger tumor volume and higher aspartate transaminase levels. Functional experiments were performed to verify the role of NONHSAT024276 in HCC progression, and the negative effects of NONHSAT024276 expression on cell proliferation and migration were identified. Mechanistically, NONHSAT024276 directly bound to polypyrimidine tract–binding protein 1 (PTBP1), downregulating it and forming a feedback loop. Furthermore, NONHSAT024276 increased the ratio of M1 and M2 isoforms of pyruvate kinase (PKM1/PKM2) and also obstructed the PTBP1/PKM‐mediated glycolysis. Finally, the rescue assays confirmed that NONHSAT024276 functioned in HCC via downregulating PTBP1 to increase the PKM1/PKM2 ratio. Hence, this study supported a model in which NONHSAT024276 downregulated PTBP1 and formed a feedback loop to increase the PKM1/PKM2 ratio to inhibit glycolysis and progression of HCC, opening new prospects for preventing or treating HCC. Abstract : This study revealed that NONHSAT024276 expression was downregulated in HCC tissues and cells. The NONHSAT024276 expression was associated with tumor progression and glycolysis. Consistent with the fact that PTBP1 played significant roles in driving metabolic reprogramming, the findings of this study suggested that NONHSAT024276/PTBP1 feedback loop increased PKM1/PKM2 ratio to inhibit tumor malignant progression and glycolysis. Therefore, this study might present new perspectives in the prevention or treatment of HCC.